2015
DOI: 10.5433/1679-0359.2015v36n2p883
|View full text |Cite
|
Sign up to set email alerts
|

Quality of milk produced by small and large dairy producers

Abstract: The aim of this study was to compare the microbiological and physicochemical quality of raw milk produced by small and large dairy producers in Paraná, Brazil. Samples of raw milk were collected from small (49) and large (21) dairy producers. Dairy farms were characterized by observation and application of questionnaires. The total bacterial count (TBC) was obtained by flow cytometry and Petrifilm® AC, while the somatic cell count (SCC) was obtained by only flow cytometry. The content of fat, proteins, lactose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 2 publications
0
15
0
3
Order By: Relevance
“…Thus, it is expected that these microorganisms resistant to the pasteurization process in its vegetative and/or sporulated form. -PERES et al (2010) compared the resistance of filamentous fungi and yeast to rapid (72°C for 20 sec) and slow (65°C for 30 min) pasteurization, as well as boiling (98°C) of milk, found that the rapid pasteurization process was the thermal treatment showing the highest resistance index (72.18%) for the yeast and filamentous fungi strains that were tested. Boiling was in second place (15.89%) and slow pasteurization third (0.99%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is expected that these microorganisms resistant to the pasteurization process in its vegetative and/or sporulated form. -PERES et al (2010) compared the resistance of filamentous fungi and yeast to rapid (72°C for 20 sec) and slow (65°C for 30 min) pasteurization, as well as boiling (98°C) of milk, found that the rapid pasteurization process was the thermal treatment showing the highest resistance index (72.18%) for the yeast and filamentous fungi strains that were tested. Boiling was in second place (15.89%) and slow pasteurization third (0.99%).…”
Section: Resultsmentioning
confidence: 99%
“…The dairy region of Castro, which includes the cities of Arapoti and Carambeí, from which originated the sample units of this work is characterized by high productivity of the herds, specialized properties and highly technified where raw milk usually has microbiological scores less than 10 CFU/mL (RIBEIRO JÚNIOR et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Each sample was collected from a different farm. These dairy farms were previously characterized (Ribeiro Júnior et al, 2015) and are part of the largest association of milk producers in southern Brazil. The milk produced on these farms is sent to the dairy company of the association for the production of noble dairy products and fluid milk.…”
Section: Methodsmentioning
confidence: 99%
“…As quantidades de proteína e lipídios são influenciadas pela raça do animal e pela sua alimentação [8], por exemplo. Já a contaminação por microrganismos causa acidificação do leite e deterioração das proteínas e lipídios [15]. Além disso, é importante lembrar que há diferentes formas de adulteração do leite que afetam a sua qualidade e segurança para o consumo.…”
Section: Qualidade Do Leiteunclassified
“…No caso da avaliação das condições higiênicas, os principais testes utilizados são: a Contagem de Células Somáticas (CCS), que indica a saúde das glândulas mamárias do animal, e a Contagem Bacteriana Total (CBT), cujo alto valor revela condições de higiene precárias na ordenha, armazenamento ou transporte do leite [15]. Para a quantificação dos componentes do leite, equipamentos baseados em técnicas de espectroscopia no infravermelho estão disponíveis no mercado e vêm substituindo métodos tradicionais que demandam tempo e reagentes químicos [17].…”
Section: Qualidade Do Leiteunclassified